(untitled) (Colloquia Comparativa Litterarum, 2025)
The fall of communism means liberty of expression, among other things. Contemporary writers tackle topics that were either considered taboo, or were censored under communism, and they portray an immediate reality that reflects everyday society. One important element is the depiction of disease in the works written after 1989, namely from a perspective that pays great attention to the body. Diseases such as AIDS and syphilis terrify people, even though they are treatable and being kept under control. Departing from Susan Sontag’s main idea from her essay Illness as Metaphor, in this article I explore the role of disease in contemporary society as depicted in two recent novels: Cruciada copiilor by Florina Ilis and Lizoanca la 11 ani by Doina Ruşti. Romanian post-communist society still avoids speaking about disease, because it is considered taboo. This avoidance most often frustrates the people afflicted by disease. One of the novels discussed in the article observes the relation between the disease and its symbolical meaning in post-communist society, and this is indicative of the problems people run into in their everyday lives. Thus, I demonstrate why disease is an important element in the reality depicted in the aforementioned novels, and I also highlight how illness becomes ore than a metaphor. It shows the institutionalized or structural arrangements in society.